Spatial pattern of soil compaction: Trees’ footprint on soil physical properties - Alameda, David; Villar, Rafael; Iriondo, José M. (Forest Ecology and Management, 2012)
Soil compaction, a determinant of forest regeneration and ecosystem functioning (e.g., biomass production), can show an aggregated spatial pattern which can be shaped by the effect of tree canopy. This work studies the inﬂuence of tree canopy type (Quercus ilex subsp. ballota, and Pinus pinaster) on the spatial distribution of variables related to soil compaction in a Mediterranean forest in southern Spain. The spatial structure of this plant-soil interaction was analyzed using the spatial analysis by distance indices methodology (SADIE). Our results showed that variables related to soil compaction, such as bulk density, penetration resistance, water content and organic matter, showed an aggregated spatial pattern which was associated to the species’ tree canopy and presence of open sites. Thus, high organic matter content and low bulk density were found under the Quercus canopy, whereas the contrary was observed under the Pinus canopy. Open sites showed similar soil properties to those than under the Pinus canopy. Soil compaction pattern and tree canopy had a clear effect on herbaceous production. In two consecutive years (2007 and 2008), herbaceous production was higher under the Quercus canopy than under the Pinus canopy. Mean values of herbaceous production in open sites were similar to those under the Quercus canopy, and no spatial association was found between open sites and herbaceous production. Structural equation modeling (SEM) was used to describe the causal relationships between tree canopy types, soil compaction related variables and herbaceous production. Results showed that tree canopy affects soil compaction variables and its effects on herbaceous production are mainly produced by a positive effect of organic matter (at 2–7 cm depth) and a negative effect of penetration resistance (at 9–14 cm depth). Therefore, forest management should consider that the replacement of one species for another or changes in tree density are likely to have important consequences in soil compaction and ecosystem functioning.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Bulk density; Herbaceous production; organic matter; Penetration resistance; Pinus pinaster; Quercus ilex

Moderate soil compaction: Implications on growth and architecture in seedlings of 17 woody plant species - Alameda, David; Villar, Rafael (Soil and Tillage Research, 2009)
Generally, soil compaction is a stress factor affecting negatively the plant growth, but its effects vary between species and with the soil compaction range. The objective of this study is to know the different growth responses of 17 woody species subjected to moderate soil compaction, because most of the studies about this subject compare the effects in treatments with a wide and discrete compaction range. We explore the effects of moderate soil compaction on a continuous scale (0.1–1.0 MPa) on seedling growth. Seedlings of 17 woody species (deciduous and evergreens) mainly from Mediterranean ecosystems were grown in near optimal conditions (light, temperature and water) in a greenhouse with a sandy substrate. In general, there was a great variability of the responses depending on the species and the studied variable. About 53% of the species showed a higher total biomass with a moderate increase in soil compaction possibly being due to a greater root–soil contact. In the same way, 41% of species increase the relative growth rate and 35% the total area. Nevertheless, in spite of these positive effects on growth, for some species (23%) there was a decrease in the root proportion with soil resistance, as result of soil strength. These effects of moderate soil compaction could sum up in two general responses of woody plants: growth increment and architecture distortion. This might be relevant as a lower root investment may be a disadvantage under drought conditions. Finally, a simple conceptual model is proposed to understand the general effects of soil compaction on growth and biomass allocation
Keywords: biomass allocation; Mediterranean ecosystem; Penetration resistance; Relative growth rate

Moderate soil compaction: Implications on growth and architecture in seedlings of 17 woody plant species - Alameda, David; Villar, Rafael (Soil and Tillage Research, 2009)
Generally, soil compaction is a stress factor affecting negatively the plant growth, but its effects vary between species and with the soil compaction range. The objective of this study is to know the different growth responses of 17 woody species subjected to moderate soil compaction, because most of the studies about this subject compare the effects in treatments with a wide and discrete compaction range. We explore the effects of moderate soil compaction on a continuous scale (0.1–1.0 MPa) on seedling growth. Seedlings of 17 woody species (deciduous and evergreens) mainly from Mediterranean ecosystems were grown in near optimal conditions (light, temperature and water) in a greenhouse with a sandy substrate. In general, there was a great variability of the responses depending on the species and the studied variable. About 53% of the species showed a higher total biomass with a moderate increase in soil compaction possibly being due to a greater root–soil contact. In the same way, 41% of species increase the relative growth rate and 35% the total area. Nevertheless, in spite of these positive effects on growth, for some species (23%) there was a decrease in the root proportion with soil resistance, as result of soil strength. These effects of moderate soil compaction could sum up in two general responses of woody plants: growth increment and architecture distortion. This might be relevant as a lower root investment may be a disadvantage under drought conditions. Finally, a simple conceptual model is proposed to understand the general effects of soil compaction on growth and biomass allocation
Keywords: biomass allocation; Mediterranean ecosystem; Penetration resistance; Relative growth rate